Electrochemistry and Chirality in Bibenzimidazole Systems. (10th October 2015) - Arnaboldi, Serena; Cirilli, Roberto; Forni, Alessandra; Gennaro, Armando; Isse, Abdirisak A.; Mihali, Voichita; Mussini, Patrizia R.; Pierini, Marco; Rizzo, Simona; Sannicolò, Francesco
Graphical abstract: THE NOVEL FAMILY OF INHERENTLY CHIRAL SUPPORTING ELECTROLYTES. Highlights: More light on the electrochemical behaviour of imidazoles and biimidazoles. Relationship between conformational properties and electroactivity in biimidazoles. Different inherent chirality and electroactivity in 1, 1'- and 2, 2'-bibenzimidazoles. CV studies of 1, 1'- bibenzimidazoles vs their single and double alkyl salts. A novel family of inherently chiral supporting electrolytes. Abstract: A detailed electrochemical study has been carried out on 1, 1'-bibenzo[ d ]imidazoles and the corresponding mono- and bibenzimidazolium salts, and compared to benzimidazole and benzimidazolium moiety models, and to 2, 2'-bibenzo[ d ]imidazole constitutional isomers. The voltammetric experiments, supported by theoretical calculations and structural diffractometric characterizations, evidence how both electrochemical and chiral properties of bibenzimidazole systems depend on the torsional barrier between the two moieties, which determines at the same time the effective conjugation and communication between symmetrical redox centres, and the possibility of obtaining the molecule in two inherently chiral enantiomers that are configurationally stable at room temperature. In particular, the 1, 1'-bibenzimidazole scaffold appears very promising for perspective development of inherently chiral substrates that may be used as additives, or supporting electrolytes, or ionic liquids. In fact, the high torsional angle granted by the 1, 1' connectivity results both in an energy barrier high enough to yield permanently stable enantiomers at room temperature, and in low effective conjugation between the two moieties, affording a very large operating window. The effect of single and double alkylation has also been considered. A preliminary enantiorecognition test, achieved performing the electrooligomerization of enantiopure 2, 2'-bi[2-(5, 2'-bithienyl)]3, 3'-bithianaphthene in the presence of either the ( R )- or the ( S )- enantiomer of a 1, 1'-bibenzimidazolium salt, has shown interesting results.